Understanding corporate social responsibility in small and medium enterprises: A bibliometric analysis of key themes and insights - Maity, Richik; Lee, Khai Loon (Springer Nature, 2026)
Despite the growing global attention to Corporate Social Responsibility (CSR) and its role in fostering sustainable development, small and medium-sized enterprises (SMEs) often face challenges in adopting such practices due to limited resources. While considerable literature exists on the impact of CSR in large corporations, its role in SMEs has been sparsely examined. This study contributes to the literature on adoption in SMEs, focusing on key factors that influence responsible practices within the unique context of smaller firms. Specifically, the study investigates the impact of governance mechanisms, supply chain pressures, certifications, and innovation on adoption in SMEs, with a particular emphasis on community engagement, relational capital, and regional social impact elements that make SME practices distinct from those in larger corporations. Using annual publication data from 629 peer-reviewed articles indexed in Scopus from 2001 to 2024, the study applies bibliometric analysis techniques such as citation, co-citation, and co-occurrence analyses using VOSviewer (version 1.6.20). The results show that, in the short run, practices in SMEs are positively influenced by governance mechanisms, certifications, and innovation. However, the long-term results indicate that governance structures, clean energy initiatives, and supply chain pressures are significant enablers of adoption. Notably, the study highlights that local, community-driven efforts by SMEs, alongside their ability to adapt strategies to regional needs, are critical to overcoming resource constraints and ensuring long-term sustainability. The study recommends prioritizing the development of tailored CSR models for SMEs that integrate sustainability, innovation, and local community engagement to drive long-term success and regional development.